Az elterelt fiatalok családi hátterének jellemzői Szabolcs-Szatmár-Bereg megyében - Barabásné Kárpáti, Dóra (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In the past 10-15 years, the consumption of illegal drugs has increased significantly both in Hungary and in our county. In parallel with the society’s getting more and more open, the fulfilment of personal freedom, and the spreading of globalisation and individual culture, the use of drugs has become more and more accessible and acceptable to the young. This study briefly overviews the family background and problems of provincial young people consuming drugs. I have studied 3 problems within this topic: family structure, relations with parents, and family members’ drug consumption behaviour. I suppose that family problems are connected with the interviewees’ alcohol and other drug consumption. In my research I apply the Euroadad questionnaire. The sample covers 144 interviewees, 76.9% of whom have been "diverted" from jurisdiction. The other respondents have volunteered for the therapy.I have processed the data with the SPSS statistical program package. Having studied the respondents’ family structure, I have found no significant difference regarding the co-habitation data for the past 30 days or the past year. The family members’ alcohol and drug consumption bears a greater relation to the use of legal drugs than of prohibited ones. The family problems related to parents are connected to the young people’s prohibited and legal drug consumption, and fathers play a particularly stressed role. The groups of party drug and amphetamine consumers struggle with more family problems than the groups of marijuana users.